Anderson localization of composite excitations in disordered optomechanical arrays - Roque, Thales Figueiredo; Peano, Vittorio; Yevtushenko, Oleg; Marquardt, Florian (New Journal of Physics, 2017)
Optomechanical (OMA) arrays are a promising future platform for studies of transport, many-body dynamics, quantum control and topological effects in systems of coupled photon and phonon modes. We introduce disordered OMA arrays, focusing on features of Anderson localization of hybrid photon-phonon excitations. It turns out that these represent a unique disordered system, where basic parameters can be easily controlled by varying the frequency and the amplitude of an external laser field. We show that the two-species setting leads to a non-trivial frequency dependence of the localization length for intermediate laser intensities. This could serve as a convincing evidence of localization in a non-equilibrium dissipative situation.
CRIS-Team Scopus Importer:2023-03-27
Keywords: disordered structures; localization; optomechanics